Tunisia : Banking System Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 1999)
This Banking System Issues paper and Statistical Appendix analyzes the banking system of Tunisia. The paper highlights that notwithstanding the gradual developments of other financial institutions such as the stock market, mutual funds, and leasing companies, the intermediation of savings and the financing of economic activity in Tunisia remains dominated by the banking system. The paper also highlights that the authorities in Tunisia are giving appropriate high priority to the modernization of the financial sector during the IXth Economic Development Plan (1997-2001).